Development and Implementation of an Online Global Pharmacovigilance Certificate Program During the COVID-19 Pandemic. (July 2022) - Doan, Thao; Lievano, Fabio; Scarazzini, Linda; Liebelt, Kate; Jaradeh, Mark; Kantarcioglu, Bulent; Fareed, Jawed; Jones, W. Keith
Pharmacovigilance plays a lifesaving role in the practice of medicine. In 2021, during the Coronavirus Infectious Disease 2019 (COVID-19) pandemic, Loyola University Chicago launched a graduate-level Pharmacovigilance Certificate Program (PV-CERT) and a pre-professional non-graduate Pharmacovigilance Certificate Course (EPEC-PV), to provide students a comprehensive and contemporary understanding of the principles and practices of pharmacovigilance. Formal training in pharmacovigilance through this course provided a structured understanding of how safety data are generated through clinical trials and from real-world evidence as well as the regulatory environment in which data are monitored and interpreted. Pharmacovigilance training is of critical importance, especially during the COVID-19 pandemic, during which several drugs were re-purposed for the management of various stages of COVID-19 without conventional safety data. Moreover, the safety of currently-used vaccines is of concern in some populations. Although anticoagulants and antithrombotic medications are crucial in the management of COVID-19, a clear pharmacovigilance program on their use in this indication is not established. As the century progresses, new diseases and infectious agents will require novel therapies for which the evaluation of benefits versus risks will be as essential as it has been for the current COVID-19 pandemic. As such, the Loyola course and accompanying programs on pharmacovigilance will play a key role in educating the next generation of professionals in pursuing careers in the development of therapies that ultimately improve patient outcomes while maintaining rigorous safety standards.